Difference Systems in Financial Futures Markets - KILCOLLIN, THOMAS ERIC (Journal of Finance, 1982)
ABSTRACT Many financial futures markets allow substitutions for the par grade of security at delivery. Substitutes are deliverable at premiums or discounts—“differences” in commodities parlance—to the futures price. The rule that establishes these differences is called a difference system. This paper characterizes financial futures market equilibrium with yield‐based difference systems and investigates particular systems in use. The major finding is that currently used difference systems effectively limit deliverable supply in the futures markets and lead to futures prices which understate the cash market price of the par security.